2012
DOI: 10.1002/ijc.27852
|View full text |Cite
|
Sign up to set email alerts
|

18β‐glycyrrhetinic acid inhibits hepatocellular carcinoma development by reversing hepatic stellate cell‐mediated immunosuppression in mice

Abstract: Hepatic stellate cells (HSCs) have immunosuppressive capabilities and contribute to the occurrence and development of hepatocellular carcinoma (HCC). Thus, activated HSCs may be a suitable target for HCC therapy. Our study used mixed leukocyte reactions (MLR) in vitro to demonstrate that 18β‐glycyrrhetinic acid (GA) could reverse HSC‐mediated immunosuppression by reducing T‐cell apoptosis and regulatory T (Treg) cells expression, thereby enhancing the ability of T cells to attack tumor cells and attenuating HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 49 publications
(62 reference statements)
0
23
0
Order By: Relevance
“…Activated HSCs that express extremely high levels of α-SMA have emerged as potent suppressors of hepatic immunity by affecting T-cell responses and thus, play a vital role in the progression of HCC (6,7,11,12). Previous studies have also indicated that activated HSCs are potential targets for HCC treatment (4). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activated HSCs that express extremely high levels of α-SMA have emerged as potent suppressors of hepatic immunity by affecting T-cell responses and thus, play a vital role in the progression of HCC (6,7,11,12). Previous studies have also indicated that activated HSCs are potential targets for HCC treatment (4). …”
Section: Discussionmentioning
confidence: 99%
“…These activated fibroblasts have been proposed to be important in promoting tumor progression and metastasis by releasing growth factors, extracellular matrix proteins and angiogenic factors (2,3). The hepatic stellate cell (HSC), an important hepatic stromal cell, is known to be activated or transdifferentiated into a myofibroblast-like cell through intercellular communication between HSCs and damaged hepatocytes in various liver tumors, including hepatocellular carcinoma (HCC) (4). These activated HSCs demonstrate a high expression of α-SMA and are considered to be a vital stromal component in HCC (5).…”
Section: Introductionmentioning
confidence: 99%
“…DMBA/TPA-induced skin tumor formation could also be suppressed by GA (Agarwal et al, 1991[2]). In addition, GA played a protective role in hepatocellular carcinoma development by reducing immunosuppression mediated by hepatic stellate cells in the tumor microenvironment (Kuang et al, 2013[18]). While GA has been shown to exhibit anti-viral and anti-inflammatory effects, it also displays cytotoxic effects on human hepatocellular carcinoma, breast cancer (Wang et al, 2015[29]) and ovarian cancer (Yang et al, 2012[31]).…”
Section: Discussionmentioning
confidence: 99%
“…13,14 18β-GA could reduce the amount of glucose release induced by glucagon in rat primary cultured hepatocytes, while 18α-GA did not. 15 Nevertheless, 11β-hydroxysteroid dehydrogenase type 1 (11β-HSD1) is a kind of microsomal enzyme belonging to the short-chain dehydrogenase/reductase family, which is highly expressed in many glucocorticoid target tissues, such as the liver, adipose tissue, skeletal muscle and macrophages.…”
Section: Introductionmentioning
confidence: 90%